Price competition and nominal illusion: Experimental evidence and a behavioural model - Antonio J. Morales; Enrique Fatas (SERIEs - Journal of the Spanish Economic Association, 2021)
The standard approach to nominal illusion in Economics sees it as a transitory phenomenon, as economic agents eventually see through the nominal veil, making the right choices. Recent empirical studies suggest that money illusion may persist, distorting real prices in a variety of economic environments, including the housing market and the stock market. In this paper, we explore the emergence and persistence of nominal illusion in an experimental entry game where firms must choose which local market to enter, and then compete in prices. All local markets are equivalent in real terms and they only differ in the currency the price competition is run under. Our experimental results show a positive, persistent and monotone effect of the nominal exchange rate on market prices, statistically significant for large enough exchange rate. We provide an explanation in terms of players simplifying the choice set using discrete grids.
Keywords: C72; C9; D43; L13; 330; Price competition; Money illusion; Experiments; Nominalrepresentation